Reconstruction of Criminal Regulation Toward Victims of Trademark Infringement in Indonesia - Wibowo, Siddiq; Susetyo, Heru; Bustani, Simona (Asian Journal of Social and Humanities, 2025)
This study examines the reconstruction of criminal law provisions governing the protection of victims in trademark infringement cases in Indonesia. The current legal framework, as stipulated in Law No. 20 of 2016 concerning Trademarks and Geographical Indications, still relies on a complaint-based offense (requiring a complaint from the aggrieved party), which limits law enforcement's proactive role and undermines the effectiveness of criminal sanctions. Through a comparative legal approach and a theoretical analysis grounded in legal certainty, proportionality, and restorative justice, this research highlights the need for systemic reform. The proposed reconstruction includes five key elements: (1) reclassifying trademark infringement from a complaint-based offense into a public criminal act, (2) implementing proportional and tiered criminal sanctions, (3) incorporating restitution as a mandatory additional penalty, (4) strengthening institutional capacity and inter-agency coordination, and (5) revising Law No. 20 of 2016 to align with international best practices. A comparative analysis of France, Singapore, and Malaysia demonstrates that integrating restitution and proactive enforcement mechanisms enhances justice for victims and strengthens the deterrent function of criminal law. This reconstruction aims to transform Indonesia’s trademark protection system into one that is more effective, fair, and adaptive to the challenges of global and digital trade ensuring both punitive and restorative justice for victims of trademark infringement in Indonesia.